Kesalahan Penggunaan Bahasa Indonesia dalam Berkomunikasi Pada Pembelajaran Via Online - Edi Syahputra; Rahma Yani; Maulida Maulida; T. Khoirunnisa. Yl; Najah Athirah (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Indonesian is a language that fulfills the elements of communication. Use oral and written communication skills Everyone has a level, but obsessed with language or different Qualities. People with language skills Optimally, all communication goals are easy to achieve. another. This applies to people who have little knowledge of the language. Communication is not a goal to be achieved, because there are often misunderstandings between the speaker and the interlocutor, this study aims to explain language errors in online learning discussion activities. The method used in this research is descriptive and qualitative. The data in this study used qualitative data in the form of words, including language errors related to spelling, punctuation, and word use. Data collection was done by three techniques: observation, listening, and taking notes. Analysis of the data used in this study begins with the collection of written data, the process of data reduction, data presentation, and drawing conclusions from the interpretation results. The results showed that students' discussion activities related to online learning found language errors in terms of spelling, punctuation, and word use. A total of 30 date sound errors were found, including: (1) Twelve errors occurred when capitalizing letters. (2) Five errors occurred when using dots. (3) Five errors occurred when using question marks. (4) Three errors were found by rewriting. (5) Found five errors in writing words. Keywords: language disability, online learning, discussion activities